Antibacterial Effect of Copaifera duckei Dwyer Oleoresin and Its Main Diterpenes against Oral Pathogens and Their Cytotoxic Effect - Abrão, Fariza; Alves, Jessica A.; Andrade, Gessica; de Oliveira, Pollyanna F.; Ambrósio, Sérgio R.; Veneziani, Rodrigo C. S.; Tavares, Denise C.; Bastos, Jairo K.; Martins, Carlos H. G. (Frontiers in Microbiology, 2018)
This study evaluates the antibacterial activity of the Copaifera duckei Dwyer oleoresin and two isolated compounds (eperu-8(20)-15,18-dioic acid and polyalthic acid) against bacteria involved in primary endodontic infections and dental caries and assesses the cytotoxic effect of these substances against a normal cell line. MIC and MBC assays pointed out the most promising metabolites for further studies on bactericidal kinetics, antibiofilm activity, and synergistic antibacterial action. The oleoresin and polyalthic acid but not eperu-8(20)-15,18-dioic provided encouraging MIC and MBC results at concentrations lower than 100 µg mL-1. The oleoresin and polyalthic acid activities depended on the evaluated strain. A bactericidal effect on L. casei (ATCC 11578 and clinical isolate) emerged before 8 h of incubation. For all the tested bacteria, the oleoresin and polyalthic acid inhibited biofilm formation by at least 50%. The oleoresin and polyalthic acid gave the best activity against A. naeslundii (ATCC 19039) and L. casei (ATCC 11578), respectively. The synergistic assays combining the oleoresin or polyalthic acid with chlorhexidine did not afford interesting results. We examined the cytotoxicity of C. duckei oleoresin, eperu-8(20)-15,18-dioic acid, and polyalthic acid against Chinese hamster lung fibroblasts. The oleoresin and polyalthic acid were cytotoxic at concentrations above 78.1 µg mL-1, whereas eperu-8(20)-15,18-dioic displayed cytotoxicity at concentrations above 312.5 µg mL-1. In conclusion, the oleoresin and polyalthic acid are potential sources of antibacterial agents against bacteria involved in primary endodontic infections and dental caries in both the sessile and the planktonic modes at concentrations that do not cause cytotoxicity.